Nurses’ perceptions of discomforts that affect the elderly in the postoperative period - Rosemary Álvares de Medeiros; Bertha Cruz Enders; Dândara Nayara Azevêdo Dantas; Ana Luisa Brandão de Carvalho Lira; Alexsandro Silva Coura; Ana Cristina Araújo de Andrade Galvão (Rev Rene)
his study aimed to identify the perceptions of hospital nurses about the concept of comfort and discomfort that affect the elderly in the postoperative period. Exploratory, descriptive research, conducted in May and June 2014, with 30 nurses from a university hospital in Natal, RN, Brazil. It was used a questionnaire based on Kolcaba’s theory of holistic comfort. Data were analyzed using descriptive statistics. Nurses (96.7%) conceptualized comfort as well-being. In the four contexts, physical, environmental, socio-cultural and psycho-spiritual, two or more discomforts were observed by more than 50% of the nurses. Pain (100%), excessive noise (56.7%), feeling of displacement of their home environment (76.7%) and anxiety (93.3%) were more frequent. The nurses identified discomforts that affect the elderly during postoperative period in the several contexts studied, with greater emphasis on physical discomforts, especially pain. The perception of the nurses surveyed about the concept of comfort demonstrates synonymy with well-being.